Behaviour of unstrengthened and DE CFRP-strengthened high-strength concrete deep beams with web openings - Sogut, Kagan; Ercan, Burcu (Frontiers in Materials, 2025)
The existing web opening created in shear span of concrete deep beams due to reasons such as accommodating utility pipes or cables resulting in a reduction in a load bearing capacity. The overall load bearing capacity can be directly affected by the extent to which arch action is interrupted in the direct load transfer to the support. Strengthening solutions have therefore appeared to enhance the load bearing capacity. However, the concrete deep beams have yet to be strengthened with the Deep Embedment (DE) Fibre Reinforced Polymer (FRP) technique. This study aims to examine the behaviour of high-strength concrete deep beams with openings, taking into account both the unstrengthened condition, and the strengthened condition with DE Carbon FRP (CFRP) bars. The finite element (FE) model was established and validated against experimental results. The FE model gave accurate predictions with a mean value of 0.97. The validated model was then used to further examine the effects of concrete strength, shear span-to-effective depth (a/d) ratio, web opening dimensions, and web opening location on the unstrengthened behaviour. Moreover, the applicability of DE CFRP bars was investigated by examining the shear force–deflection response, FRP bar diameter, and FRP bar configuration. Increasing the concrete strength from 40 to 100 MPa resulted in an improvement in shear force capacity of up to approximately 45.5%. An increase in the a/d ratio from 1.08 to 2.7 resulted in a reduction in the shear force capacity by about 50%. The findings showed that the load transfer to the support through direct compression was increasingly disrupted in concrete deep beams as web openings became larger. Shear resistance was directly affected by the position of the web opening. The position of web opening affected the continuity of the load path from the load application point to the support. The use of CFRP bars instigated an enhancement of the shear force capacity of up to 33.8%. Shear resistance also increased as bar diameter was increased. Finally, the design guidance predictions were evaluated, and it was found that the design guidance significantly overestimated the DE CFRP-strengthened shear force capacity.